Feasible strategy for the nitrogen fixation and humification quality improvement by spent mushroom substrate as conditioning agent - Ai, Shuang; Zhang, Yuanbei; Zheng, Guoxiang (International Journal of Agricultural and Biological Engineering, 2024)
There is an overlooked problem which increasing microbial abundance while reducing nitrogen loss during composting. This study investigated the viability of spent mushroom substrate (SMS) as conditioners in the aerobic composting of kitchen waste (KW) with cattle manure (CM). The variation of temperature, pH, C/N, organic matter, cellulose, hemicelluloses, germination index (GI), and microflora structure were explored to evaluate the potential in accelerating maturity and nitrogen fixation by SMS addition. The results showed that the addition of SMS accelerated the heating rate, prolonged the high temperature time, and decreased organic matter, hemicellulose, and cellulose by 17.49%, 23.61%, and 18.62%, respectively. The GI reached 105.86% with SMS addition, while 74.17% was found in control treatment after composting. SMS changed the microbial community composition and increased the species abundance. Proteiniclasticum, Clostridium XI and Azomonas were dominant bacteria, which increased the retention of nitrogen, promoted organic matter degradation and reduce compost time. The study can provide a feasible strategy for nitrogen fixation in the field of organic waste recycling. Keywords: spent mushroom substrate, conditioning agent, nitrogen fixation, humification quality, aerobic composting DOI: 10.25165/j.ijabe.20241703.7790 Citation: Ai S, Zhang Y B, Zhng G X. Feasible strategy for the nitrogen fixation and humification quality improvement by spent mushroom substrate as conditioning agent. Int J Agric & Biol Eng, 2024; 17(3): 235-240.